Hadith #106 - Sahih al-Bukhari - Ali ibn Abi Talib (Sahih al-Bukhari)
The Prophet (ï·º) said, âDo not tell a lie against me for whoever tells a lie against me (intentionally) then he will surely enter the Hell-fire.â
Grade: Sahih

Hadith #132 - Sahih al-Bukhari - Ali ibn Abi Talib (Sahih al-Bukhari)
I used to get the emotional urethral discharge frequently so I requested Al-Miqdad to ask the Prophet (ï·º) about it. Al-Miqdad asked him and he replied, âOne has to perform ablution (after it).â (See Hadith No. 269).
Grade: Sahih

Hadith #178 - Sahih al-Bukhari - Ali ibn Abi Talib (Sahih al-Bukhari)
I used to get emotional urethral discharges frequently and felt shy to ask Allahâs Messenger (ï·º) about it. So I requested Al-Miqdad bin Al-Aswad to ask (the Prophet (ï·º) ) about it. Al-Miqdad asked him and he replied, âOne has to perform ablution (after it).â
Grade: Sahih

Hadith #269 - Sahih al-Bukhari - Ali ibn Abi Talib (Sahih al-Bukhari)
I used to get emotional urethral discharge frequently. Being the son-in-law of the Prophet (ï·º) I requested a man to ask him about it. So the man asked the Prophet (ï·º) about it. The Prophet (ï·º) replied, âPerform ablution after washing your organ (penis).â
Grade: Sahih

Hadith #1094 - Sahih al-Bukhari - Ali ibn Abi Talib (Sahih al-Bukhari)
One night Allahâs Messenger (ï·º) came to me and Fatima, the daughter of the Prophet (ï·º) and asked, âWonât you pray (at night)?â I said, âO Allahâs Messenger (ï·º)! Our souls are in the hands of Allah and if He wants us to get up He will make us get up.â When I said that, he left us without saying anything and I heard that he was hitting his thigh and saying, âBut man is more quarrelsome than anything.â (18.54)
Grade: Sahih

Hadith #1315 - Sahih al-Bukhari - Ali ibn Abi Talib (Sahih al-Bukhari)
â We were accompanying a funeral procession in Baqi-I-Gharqad. The Prophet (ï·º) came to us and sat and we sat around him. He had a small stick in his hand then he bent his head and started scraping the ground with it. He then said, âThere is none among you, and not a created soul, but has place either in Paradise or in Hell assigned for him and it is also determined for him whether he will be among the blessed or wretched.â A man said, âO Allahâs Messenger (ï·º)! Should we not depend
Grade: Sahih

Hadith #1645 - Sahih al-Bukhari - Ali ibn Abi Talib (Sahih al-Bukhari)
Allahâs Messenger (ï·º) ordered me to give in charity the skin and the coverings of the Budn which I had slaughtered.
Grade: Sahih

Hadith #1654 - Sahih al-Bukhari - Ali ibn Abi Talib (Sahih al-Bukhari)
The Prophet (ï·º) sent me to supervise the (slaughtering of) Budn (Hadi camels) and ordered me to distribute their meat, and then he ordered me to distribute their covering sheets and skins. âAll added, âThe Prophet (ï·º) ordered me to supervise the slaughtering (of the Budn) and not to give anything (of their bodies) to the butcher as wages for slaughtering.â
Grade: Sahih

Hadith #1655 - Sahih al-Bukhari - Ali ibn Abi Talib (Sahih al-Bukhari)
The Prophet (ï·º) ordered me to supervise the (slaughtering) of Budn (Hadi camel) and to distribute their meat, skins and covering sheets in charity and not to give anything (of their bodies) to the butcher as wages for slaughtering.
Grade: Sahih

Hadith #1656 - Sahih al-Bukhari - Ali ibn Abi Talib (Sahih al-Bukhari)
The Prophet (ï·º) offered one hundred Budn as Hadi and ordered me to distribute their meat (in charity) and I did so. Then he ordered me to distribute their covering sheets in charity and I did so. Then he ordered me to distribute their skins in charity and I did so.
Grade: Sahih

Hadith #1802 - Sahih al-Bukhari - Ali ibn Abi Talib (Sahih al-Bukhari)
We have nothing except the Book of Allah and this written paper from the Prophet (wherein is written:) Medina is a sanctuary from the âAir Mountain to such and such a place, and whoever innovates in it an heresy or commits a sin, or gives shelter to such an innovator in it will incur the curse of Allah, the angels, and all the people, none of his compulsory or optional good deeds of worship will be accepted. And the asylum (of protection) granted by any Muslim is to be secured (respected) by a
Grade: Sahih

Hadith #2014 - Sahih al-Bukhari - Ali ibn Abi Talib (Sahih al-Bukhari)
I got an old she-camel as my share from the booty, and the Prophet (ï·º) had given me another from Al- Khumus. And when I intended to marry Fatima (daughter of the Prophet), I arranged that a goldsmith from the tribe of Bani Qainuqaâ would accompany me in order to bring Idhkhir and then sell it to the goldsmiths and use its price for my marriage banquet.
Grade: Sahih

Hadith #2213 - Sahih al-Bukhari - Ali ibn Abi Talib (Sahih al-Bukhari)
Allahâs Messenger (ï·º) ordered me to distribute the saddles and skins of the Budn which I had slaughtered.
Grade: Sahih

Hadith #2510 - Sahih al-Bukhari - Ali ibn Abi Talib (Sahih al-Bukhari)
The Prophet (ï·º) gave me a silken dress as a gift and I wore it. When I saw the signs of anger on his face, I cut it into pieces and distributed it among my wives.â
Grade: Sahih

Hadith #2788 - Sahih al-Bukhari - Ali ibn Abi Talib (Sahih al-Bukhari)
I never saw the Prophet (ï·º) saying, âLet my parents sacrifice their lives for you,â to any man after Sa`d. I heard him saying (to him), âThrow (the arrows)! Let my parents sacrifice their lives for you.â
Grade: Sahih

Hadith #2813 - Sahih al-Bukhari - Ali ibn Abi Talib (Sahih al-Bukhari)
When it was the day of the battle of Al-Ahzab (i.e. the clans), Allahâs Messenger (ï·º) said, âO Allah! Fill their (i.e. the infidelsâ) houses and graves with fire as they busied us so much that we did not perform the prayer (i.e. `Asr) till the sun set.â
Grade: Sahih

Hadith #2964 - Sahih al-Bukhari - Ali ibn Abi Talib (Sahih al-Bukhari)
I got a she-camel in my share of the war booty on the day (of the battle) of Badr, and the Prophet (ï·º) had given me a she-camel from the Khumus. When I intended to marry Fatima, the daughter of Allahâs Apostle, I had an appointment with a goldsmith from the tribe of Bani Qainuqaâ to go with me to bring Idhkhir (i.e. grass of pleasant smell) and sell it to the goldsmiths and spend its price on my wedding party. I was collecting for my she-camels equipment of saddles, sacks and ropes while m
Grade: Sahih

Hadith #2985 - Sahih al-Bukhari - Ali ibn Abi Talib (Sahih al-Bukhari)
Fatima complained of what she suffered from the hand mill and from grinding, when she got the news that some slave girls of the booty had been brought to Allahâs Messenger (ï·º). She went to him to ask for a maid-servant, but she could not find him, and told `Aisha of her need. When the Prophet (ï·º) came, Aisha informed him of that. The Prophet (ï·º) came to our house when we had gone to our beds. (On seeing the Prophet) we were going to get up, but he said, âKeep at your places,â I felt
Grade: Sahih

Hadith #3047 - Sahih al-Bukhari - Ali ibn Abi Talib (Sahih al-Bukhari)
We did not, write anything from the Prophet (ï·º) except the Qurâan and what is written in this paper, (wherein) the Prophet (ï·º) said, âMedina is a sanctuary from (the mountain of) Air to so and-so, therefore, whoever innovates (in it) an heresy or commits a sin, or gives shelter to such an innovator, will incur the Curse of Allah. the angels and all the people; and none of his compulsory or optional good deeds of worship will be accepted And the asylum granted by any Muslim Is to be secur
Grade: Sahih

Hadith #3290 - Sahih al-Bukhari - Ali ibn Abi Talib (Sahih al-Bukhari)
I heard the Prophet (ï·º) saying, âMary, the daughter of `Imran, was the best among the women (of the world of her time) and Khadija is the best amongst the women. (of this nation).
Grade: Sahih

Hadith #3459 - Sahih al-Bukhari - Ali ibn Abi Talib (Sahih al-Bukhari)
I relate the traditions of Allahâs Messenger (ï·º) to you for I would rather fall from the sky than attribute something to him falsely. But when I tell you a thing which is between you and me, then no doubt, war is guile. I heard Allahâs Messenger (ï·º) saying, âIn the last days of this world there will appear some young foolish people who will use (in their claim) the best speech of all people (i.e. the Qurâan) and they will abandon Islam as an arrow going through the game. Their belief
Grade: Sahih

Hadith #3547 - Sahih al-Bukhari - Ali ibn Abi Talib (Sahih al-Bukhari)
Fatima complained of the suffering caused to her by the hand mill. Some Captives were brought to the Prophet, she came to him but did not find him at home `Aisha was present there to whom she told (of her desire for a servant). When the Prophet (ï·º) came, Aisha informed him about Fatimaâs visit. `Ali added âSo the Prophet (ï·º) came to us, while we had gone to our bed I wanted to get up but the Prophet (ï·º) said, âRemain at your placeâ. Then he sat down between us till I found the cool
Grade: Sahih

Hadith #3652 - Sahih al-Bukhari - Ali ibn Abi Talib (Sahih al-Bukhari)
I heard Allahâs Messenger (ï·º) saying (as below) Narrated `Ali: The Prophet (ï·º) said, âThe best of the worldâs women is Mary (at her lifetime), and the best of the worldâs women is Khadija (at her lifetime).
Grade: Sahih

Hadith #3804 - Sahih al-Bukhari - Ali ibn Abi Talib (Sahih al-Bukhari)
The following Holy Verse:â âThese two opponents (believers and disbelievers) dispute with each other about their Lord.â (22.19) was revealed concerning us.
Grade: Sahih

Hadith #3818 - Sahih al-Bukhari - Ali ibn Abi Talib (Sahih al-Bukhari)
Allahâs Messenger (ï·º) sent me, Abu Marthad and Az-Zubair, and all of us were riding horses, and said, âGo till you reach Raudat-Khakh where there is a pagan woman carrying a letter from Hatib bin Abi Baltaâ a to the pagans of Mecca.â So we found her riding her camel at the place which Allahâs Messenger (ï·º) had mentioned. We said (to her),â(Give us) the letter.â She said, âI have no letter.â Then we made her camel kneel down and we searched her, but we found no letter. Then
Grade: Sahih

Hadith #3838 - Sahih al-Bukhari - Ali ibn Abi Talib (Sahih al-Bukhari)
I had a she-camel which I got in my share from the booty of the battle of Badr, and the Prophet (ï·º) had given me another she camel from the Khumus which Allah had bestowed on him that day. And when I intended to celebrate my marriage to Fatima, the daughter of the Prophet, I made an arrangement with a goldsmith from Bani Qainuqa âthat he should go with me to bring Idhkhir (i.e. a kind of grass used by gold-smiths) which I intended to sell to gold-smiths in order to spend its price on the mar
Grade: Sahih

Hadith #3888 - Sahih al-Bukhari - Ali ibn Abi Talib (Sahih al-Bukhari)
I have never heard the Prophet (ï·º) mentioning both his father and mother for anybody other than Sa`d.
Grade: Sahih

Hadith #3889 - Sahih al-Bukhari - Ali ibn Abi Talib (Sahih al-Bukhari)
I have never heard the Prophet (ï·º) mentioning his father and mother for anybody other than Sa`d bin Malik. I heard him saying on the day of Uhud, âO Sa`d throw (arrows)! Let my father and mother be sacrificed for you !â
Grade: Sahih

Hadith #3939 - Sahih al-Bukhari - Ali ibn Abi Talib (Sahih al-Bukhari)
On the day of Al-Khandaq (i.e. Trench), the Prophet (ï·º) said â(Let) Allah fill their (i.e. the infidelsâ) houses and graves with fire just as they have prevented us from offering the Middle Prayer (i.e. `Asr prayer) till the sun had set.â
Grade: Sahih

Hadith #4040 - Sahih al-Bukhari - Ali ibn Abi Talib (Sahih al-Bukhari)
On the day of Khaibar, Allahâs Messenger (ï·º) forbade the Mutâa (i.e. temporary marriage) and the eating of donkey-meat.
Grade: Sahih

Hadith #4092 - Sahih al-Bukhari - Ali ibn Abi Talib (Sahih al-Bukhari)
Allahâs Messenger (ï·º) sent me, Az-Zubair and Al-Miqdad saying, âProceed till you reach Rawdat Khakh where there is a lady carrying a letter, and take that (letter) from her.â So we proceeded on our way with our horses galloping till we reached the Rawda, and there we found the lady and said to her, âTake out the letter.â She said, âI have no letter.â We said, âTake out the letter, or else we will take off your clothes.â So she took it out of her braid, and we brought the lett
Grade: Sahih

Hadith #4153 - Sahih al-Bukhari - Ali ibn Abi Talib (Sahih al-Bukhari)
The Prophet (ï·º) sent a Sariya under the command of a man from the Ansar and ordered the soldiers to obey him. He (i.e. the commander) became angry and said âDidnât the Prophet (ï·º) order you to obey me!â They replied, âYes.â He said, âCollect fire-wood for me.â So they collected it. He said, âMake a fire.â When they made it, he said, âEnter it (i.e. the fire).â So they intended to do that and started holding each other and saying, âWe run towards (i.e. take refuge with
Grade: Sahih

Hadith #4328 - Sahih al-Bukhari - Ali ibn Abi Talib (Sahih al-Bukhari)
On the day of Al-Khandaq (the battle of the Trench). the Prophet (ï·º) said, âThey (i.e. pagans prevented us from offering the middle (the Best) Prayer till the sun had set. May Allah fill their graves, their houses (or their bodies) with fire.â
Grade: Sahih

Hadith #4518 - Sahih al-Bukhari - Ali ibn Abi Talib (Sahih al-Bukhari)
That one night Allahâs Messenger (ï·º) came to him and Fatima and said, âDonât you (both offer the (Tahajjud) prayer?â `Ali said, âWhen Allah wishes us to get up, we get up.â The Prophet (ï·º) then recited: âBut man is more quarrelsome than anything.â (18.54) (See Hadith No. 227,Vol. 2)
Grade: Sahih

Hadith #4682 - Sahih al-Bukhari - Ali ibn Abi Talib (Sahih al-Bukhari)
Allahâs Messenger (ï·º) sent me along with AzZubair and Al-Miqdad and said, âProceed till you reach a place called Raudat-Khakh where there is a lady travelling in a howda on a camel. She has a letter. Take the letter from her.â So we set out, and our horses ran at full pace till we reached Raudat Khakh, and behold, we saw the lady and said (to her), âTake out the letter!â She said, âI have no letter with me.â We said, âEither you take out the letter or we will strip you of your
Grade: Sahih

Hadith #4738 - Sahih al-Bukhari - Ali ibn Abi Talib (Sahih al-Bukhari)
We were in the company of the Prophet (ï·º) in a funeral procession at Baqi Al-Gharqad. He said, âThere is none of you but has his place written for him in Paradise or in the Hell- Fire.â They said, âO Allahâs Apostle! Shall we depend (on this fact and give up work)?â He said, âCarry on doing (good deeds), for every body will find it easy to do (what will lead him to his destined place).â Then he recited: âAs for him who gives (in charity) and keeps his duty to Allah, and believe
Grade: Sahih

Hadith #4740 - Sahih al-Bukhari - Ali ibn Abi Talib (Sahih al-Bukhari)
While the Prophet (ï·º) was in a funeral procession, he took a small stick and started scraping the earth with it and said, âThere is none among you but has his place written for him, either in the Hell Fire or in Paradise.â They (the people) said, âAllahâs Messenger (ï·º)! Shall we depend on this (and leave work)?â He replied. âCarry on doing (good deeds), for everybody will find easy (to do) such deeds as will lead him to his destined place.â The Prophet (ï·º) then recited:â â
Grade: Sahih

Hadith #4741 - Sahih al-Bukhari - Ali ibn Abi Talib (Sahih al-Bukhari)
We were in the company of the Prophet (ï·º) and he said, âThere is none among you but has his place written for him, either in Paradise or in the Hell-Fire.â We said, âO Allahâs Messenger (ï·º)! Shall we depend (on this fact and give up work)?â He replied, âNo! Carry on doing good deeds, for everybody will find easy (to do) such deeds as will lead him to his destined place.â Then the Prophet (ï·º) recited: âAs for him who gives (in charity) and keeps his duty to Allah, and believ
Grade: Sahih

Hadith #4742 - Sahih al-Bukhari - Ali ibn Abi Talib (Sahih al-Bukhari)
While we were in a funeral procession in Baqi Al-Gharqad, Allahâs Messenger (ï·º) came and sat down, and we sat around him. He had a small stick in his hand and he bent his head and started scraping the ground with it. He then said, âThere is none among you, and no created soul but has his place written for him either in Paradise or in the Hell-Fire, and also has his happy or miserable fate (in the Hereafter) written for him.â A man said, âO Allahâs Messenger (ï·º)! Shall we depend upo
Grade: Sahih

Hadith #4743 - Sahih al-Bukhari - Ali ibn Abi Talib (Sahih al-Bukhari)
While the Prophet (ï·º) was in a funeral procession. he picked up something and started scraping the ground with it, and said, âThere is none among you but has his place written for him either in the Hell Fire or in Paradise.â They said, âO Allahâs Messenger (ï·º)! Shall we not depend upon what has been written for us and give up deeds? He said, âCarry on doing (good) deeds, for everybody will find easy to do such deeds as will lead him to his destined place for which he has been creat
Grade: Sahih

Hadith #4853 - Sahih al-Bukhari - Ali ibn Abi Talib (Sahih al-Bukhari)
I heard the Prophet (ï·º) saying, âIn the last days (of the world) there will appear young people with foolish thoughts and ideas. They will give good talks, but they will go out of Islam as an arrow goes out of its game, their faith will not exceed their throats. So, wherever you find them, kill them, for there will be a reward for their killers on the Day of Resurrection.â
Grade: Sahih

Hadith #4910 - Sahih al-Bukhari - Ali ibn Abi Talib (Sahih al-Bukhari)
I said to Ibn `Abbas, âDuring the battle of Khaibar the Prophet (ï·º) forbade (Nikah) Al-Mutâa and the eating of donkeyâs meat.â
Grade: Sahih

Hadith #5147 - Sahih al-Bukhari - Ali ibn Abi Talib (Sahih al-Bukhari)
Fatima went to the Prophet (ï·º) complaining about the bad effect of the stone hand-mill on her hand. She heard that the Prophet (ï·º) had received a few slave girls. But (when she came there) she did not find him, so she mentioned her problem to `Aisha. When the Prophet (ï·º) came, `Aisha informed him about that. `Ali added, âSo the Prophet (ï·º) came to us when we had gone to bed. We wanted to get up (on his arrival) but he said, âStay where you are.â Then he came and sat between me and
Grade: Sahih

Hadith #5148 - Sahih al-Bukhari - Ali ibn Abi Talib (Sahih al-Bukhari)
Fatima came to the Prophet (ï·º) asking for a servant. He said, âMay I inform you of something better than that? When you go to bed, recite âSubhan Allahâ thirty three times, âAl hamduli l-lahâ thirty three times, and âAllahu Akbarâ thirty four times. `Ali added, âI have never failed to recite it ever since.â Somebody asked, âEven on the night of the battle of Siffin?â He said, âEven on the night of the battle of Siffin.â
Grade: Sahih

Hadith #5152 - Sahih al-Bukhari - Ali ibn Abi Talib (Sahih al-Bukhari)
The Prophet (ï·º) gave me a silk suit and I wore it, but when I noticed anger on his face, I cut it and distributed it among my women-folk.
Grade: Sahih

Hadith #5311 - Sahih al-Bukhari - Ali ibn Abi Talib (Sahih al-Bukhari)
Allahâs Messenger (ï·º) prohibited Al-Mutâa marriage and the eating of donkeyâs meat in the year of the Khaibar battle.
Grade: Sahih

Hadith #5381 - Sahih al-Bukhari - Ali ibn Abi Talib (Sahih al-Bukhari)
the Prophet (ï·º) forbade the use of Ad-Dubbaâ and Al Muzaffat. Aâmash also narrated this.
Grade: Sahih

Hadith #5567 - Sahih al-Bukhari - Ali ibn Abi Talib (Sahih al-Bukhari)
The Prophet (ï·º) asked for his Rida, put it on and set out walking. Zaid bin Haritha and I followed him till he reached the house where Harnza (bin `Abdul Muttalib) was present and asked for permission to enter, and they gave us permission.
Grade: Sahih

Hadith #5613 - Sahih al-Bukhari - Ali ibn Abi Talib (Sahih al-Bukhari)
The Prophet (ï·º) gave me a silk suit. I went out wearing it, but seeing the signs of anger on his face, I tore it and distributed it among my wives.
Grade: Sahih

Hadith #5949 - Sahih al-Bukhari - Ali ibn Abi Talib (Sahih al-Bukhari)
I never heard Allahâs Messenger (ï·º) saying, âLet my father and mother be sacrificed for you,â except for Sa`d (bin Abi Waqqas). I heard him saying, âThrow! (arrows), Let my father and mother be sacrificed for you !â (The sub-narrator added, âI think that was in the battle of Uhud.â)
Grade: Sahih

Hadith #5982 - Sahih al-Bukhari - Ali ibn Abi Talib (Sahih al-Bukhari)
We were with the Prophet (ï·º) in a funeral procession, and he started scraping the ground with a small stick and said, âThere is none amongst you but has been assigned a place (either) in Paradise and (or) in the Hell-Fire.â The people said (to him), âShould we not depend upon it?â He said: carry on doing (good) deeds, for everybody will find easy such deeds as will lead him to his destined place. He then recited: âAs for him who gives (in charity) and keeps his duty to Allah..â (92
Grade: Sahih

Hadith #6024 - Sahih al-Bukhari - Ali ibn Abi Talib (Sahih al-Bukhari)
Allahâs Messenger (ï·º) sent me, Az-Zubair bin Al-Awwam and Abu Marthad Al-Ghanawi, and all of us were horsemen, and he said, âProceed till you reach Rawdat Khakh, where there is a woman from the pagans carrying a letter sent by Hatib bin Abi Baltaâa to the pagans (of Mecca).â So we overtook her while she was proceeding on her camel at the same place as Allahâs Messenger (ï·º) told us. We said (to her) âWhere is the letter which is with you?â She said, âI have no letter with me.â
Grade: Sahih

Hadith #6081 - Sahih al-Bukhari - Ali ibn Abi Talib (Sahih al-Bukhari)
Fatima complained about the blisters on her hand because of using a mill-stone. She went to ask the Prophet for servant, but she did not find him (at home) and had to inform `Aisha of her need. When he came, `Aisha informed him about it. `Ali added: The Prophet (ï·º) came to us when we had gone to our beds. When I was going to get up, he said, ââStay in your places,â and sat between us, till I felt the coolness of the feet on my chest. The Prophet (ï·º) then said, âShall I not tell you o
Grade: Sahih

Hadith #6157 - Sahih al-Bukhari - Ali ibn Abi Talib (Sahih al-Bukhari)
We were in the company of the Prophet (ï·º) on the day (of the battle) of Al-Khandaq (the Trench). The Prophet said, âMay Allah fill their (the infidelsâ) graves and houses with fire, as they have kept us so busy that we could not offer the middle prayer till the sun had set; and that prayer was the `Asr prayer.â
Grade: Sahih

Hadith #6364 - Sahih al-Bukhari - Ali ibn Abi Talib (Sahih al-Bukhari)
While we were sitting with the Prophet (ï·º) who had a stick with which he was scraping the earth, he lowered his head and said, âThere is none of you but has his place assigned either in the Fire or in Paradise.â Thereupon a man from the people said, âShall we not depend upon this, O Allahâs Apostle?â The Prophet (ï·º) said, âNo, but carry on and do your deeds, for everybody finds it easy to do such deeds (as will lead him to his place).â The Prophet (ï·º) then recited the Verse:
Grade: Sahih

Hadith #6510 - Sahih al-Bukhari - Ali ibn Abi Talib (Sahih al-Bukhari)
We have no Book to recite except the Book of Allah (Qurâan) and this paper. Then `Ali took out the paper, and behold ! There was written in it, legal verdicts about the retaliation for wounds, the ages of the camels (to be paid as Zakat or as blood money). In it was also written: âMedina is a sanctuary from Air (mountain) to Thaur (mountain). So whoever innovates in it an heresy (something new in religion) or commits a crime in it or gives shelter to such an innovator, will incur the curse o
Grade: Sahih

Hadith #6532 - Sahih al-Bukhari - Ali ibn Abi Talib (Sahih al-Bukhari)
I would not feel sorry for one who dies because of receiving a legal punishment, except the drunk, for if he should die (when being punished), I would give blood money to his family because no fixed punishment has been ordered by Allahâs Messenger (ï·º) for the drunk.
Grade: Sahih

Hadith #6673 - Sahih al-Bukhari - Ali ibn Abi Talib (Sahih al-Bukhari)
Whenever I tell you a narration from Allahâs Messenger (ï·º), by Allah, I would rather fall down from the sky than ascribe a false statement to him, but if I tell you something between me and you (not a Hadith) then it was indeed a trick (i.e., I may say things just to cheat my enemy). No doubt I heard Allahâs Apostle saying, âDuring the last days there will appear some young foolish people who will say the best words but their faith will not go beyond their throats (i.e. they will have no
Grade: Sahih

Hadith #6876 - Sahih al-Bukhari - Ali ibn Abi Talib (Sahih al-Bukhari)
The Prophet (ï·º) sent an army unit (for some campaign) and appointed a man from the Ansar as its commander and ordered them (the soldiers) to obey him. (During the campaign) he became angry with them and said, âDidnât the Prophet (ï·º) order you to obey me?â They said, âYes.â He said, âI order you to collect wood and make a fire and then throw yourselves into it.â So they collected wood and made a fire, but when they were about to throw themselves into, it they started looking at
Grade: Sahih

Hadith #6983 - Sahih al-Bukhari - Ali ibn Abi Talib (Sahih al-Bukhari)
The Prophet (ï·º) , sent an army and appointed some man their commander The man made a fire and then said (to the soldiers), âEnter it.â Some of them intended to enter it while some others said, âWe have run away from it (i.e., embraced Islam to save ourselves from the âfireâ).â They mentioned that to the Prophet, and he said about people who had intended to enter the fire. âIf they had entered it, they would have remained In it till the Day of Resurrection.â Then he said to othe
Grade: Sahih

Hadith #7067 - Sahih al-Bukhari - Ali ibn Abi Talib (Sahih al-Bukhari)
That Allahâs Messenger (ï·º) came to him and Fatima the daughter of Allahâs Messenger (ï·º) at their house at night and said, âWonât you pray?â `Ali replied, âO Allahâs Messenger (ï·º)! Our souls are in the Hands of Allah and when he wants us to get up, He makes us get up.â When `Ali said that to him, Allahâs Messenger (ï·º) left without saying anything to him. While the Prophet (ï·º) was leaving, `Ali heard him striking his thigh (with his hand) and saying, âBut man is quarr
Grade: Sahih

Hadith #7180 - Sahih al-Bukhari - Ali ibn Abi Talib (Sahih al-Bukhari)
That one night Allahâs Messenger (ï·º) visited him and Fatima, the daughter of Allahâs Messenger (ï·º) and said to them, âWon ât you offer (night) prayer?.. `Ali added: I said, âO Allahâs Messenger (ï·º)! Our souls are in the Hand of Allah and when He Wishes to bring us to life, He does.â Then Allahâs Messenger (ï·º) went away when I said so and he did not give any reply. Then I heard him on leaving while he was striking his thighs, saying, âBut man is, more quarrelsome than an
Grade: Sahih

Hadith #7266 - Sahih al-Bukhari - Ali ibn Abi Talib (Sahih al-Bukhari)
While the Prophet (ï·º) was in a funeral procession, he took a stick and started scraping the earth with it and said, âThere is none of you but has his place assigned either in Hell or in Paradise.â They (the people) said, âShall we not depend upon that (and give up doing any deeds)?â He said, â Carry on doing (good deeds) for everybody will find it easy to do such deeds as will lead him to his destined place for which he has been created .â (And then the Prophet (ï·º) recited the Ve
Grade: Sahih